PENYEDERHANAAN SISTEM KEPARTAIAN PASCA ORDE BARU - Suwarko, Andi (Jurnal Review Politik, 2013)
The party system in post new order was shifted from extreme multi-party system in the 1999, 2004, 2009 general elections into a simple multi-party system in the 2014 election. The distance of ideology was shifted also from a system of moderate pluralism into simple pluralism. This research seeks to examine: first, the implications of a multi-party system after the new order; second, the solution to overcome the implications of multi-party case. Research findings: first, the implications of a multi-party system were the absence of the majority party in parliament. President-elected often not of the party was winning in election, which eventually form a coalition to secure a policy and political stability. Second, to overcome the problem was making simplification of the party system with two approaches, the approaches “by nature” and “by design”.